Upgrading of thiophenic compounds from fuels over a silver-modified MoO3 catalyst under ambient conditions. (1st November 2021) - Miao, Guang; Chong, Peng; Yang, Cuiting; Liu, Zewei; Yu, Hao; Dong, Lei; Li, Guoqing; Xiao, Jing
Highlights: The catalytic upgrading of thiophenic sulfur compounds in fuel was explored by using silver-modified MoO3 under ambient conditions. H2 O2 /HBr mixture was employed as the green bromination agent. The formation of dibromides was promoted by the active MoAgO4 identified on MoO3 . DFT calculations reveal the selective bromination of thiophene to mono-bromothiophene, and the subsequent 2, 5-dibromothiophene was achieved on the MoO3 (111) and MoAg2 O4 (111) sites, respectively. Abstract: The demand for heterocyclic sulfur compounds is increasingly in fine chemical industry, where the thiophenic sulfur impurities in fuels can be a potential recyclable feedstock. In this work, the catalytic upgrading of thiophenic sulfur compounds over a silver-modified MoO3 catalyst under ambient conditions was reported. Br2 and H2 O2 /HBr were used to convert thiophenic compounds in alkane and alcohol solutions. The conversion of various thiophenic compounds (thiophene, benzothiophene and dibenzothiophene) to the corresponding bromides reached up to 81.6 99.8%. The bromination path undergoes electrophilic substitution mechanism, and the transformation of mono- to dibromides is identified as the rate-determining step. The introduction of MoAg2 O4 phase on MoO3 is rationalized to boost the conversion of mono-bromothiophene, which results in the selectivity of 2, 5-dibromothiophene increased from 10% to over 50%. The optimized silver loading was 10% due to its high thiophene conversion and selectivity of dibromides. Silver modification of MoO3 rods not only stabilized the textural property of catalysts but also improved its bromination activity compared to the bulk MoO3 indicated by SEM and FTIR characterization. Density functional theory (DFT) calculation suggested that the formation of 2-bromothiphene and 2, 5-dibromothiophene were preferred on the MoO3 (111) and MoAg2 O4 (111) sites, respectively. The catalytic upgrading approach paves the way for the efficient utilization of thiophenic sulfur impurities in fuels to their value-added under mild conditions.